A Demograpidc Study of Elephant Population in Periyar Tiger Reserve and Adjacent Areas in Kerala - Easa, P. S.; Jahas, S. A. Sabu (Indian Forester, 2002)
A study was carried out in Periyar Tiger Reserve and adjacent areas of Ranni, Konni and Achenkovil Forest Divisions in 1997 to collect information on the herd composition, sex ratio, density and population of elephants. This area forms the portion of Elephant Reserve No.10. The area mainly comprises tropical wet evergreen and grassland, followed by deciduous forests. Information on herd size, composition and structure of elephants were collected through direct observations. The individuals were classified into different age-sex categories. Line transact method was followed to collect information on dung density. A total of 379 elephants were sighted in 63 herds. Herd size of elephant ranged from 1 to 19. About 14% were loners. Twenty eight adult males sighted constituted 7.39% of the population. About 50% of the males were ’Makhnas’ and remaining tuskers in a proportion of 1:1. Adult females formed 58.58% of the population followed by sub-adult females. The overall male to female sex ratio was 1:8.68 and adult male to female 1: 7.93. The overall sex ratio of elephants in Periyar Tiger Reserve alone was 1:11.50. The overall elephant density was 0.50lkm2in the study area and the density was comparatively higher in grasslands (0.89lkm2).